Impact of Governance, Legal System and Economic Freedom on Foreign Investment in the MENA Region - Kobeissi, Nada (Journal of Comparative International Management, 2005)
Abstract While there is substantial literature examining the flow of foreign investments into various regions of the world, there is still lack of research focus on foreign investment activities in the Middle East and North Africa (MENA). One objective of this paper is to remedy this neglect and extend previous empirical work by focusing on foreign investments in that region. The second objective is to focus on non-traditional determinants that have tended to be overlooked or underestimated in previous research. The paper will focus on factors such as governance, legal environment, and economic freedom and examine their impact on foreign investment activities in the MENA region.